Evaluation of HOXA group gene expression in endometrium of women with endometriosis - Szczepańska, Małgorzata; Wirstlein, Przemysław; Skrzypczak, Jana (Menopause Review/Przegląd Menopauzalny, 2007)
The aetiology of infertility in patients with endometriosis is not fully explained. HOXA-10 and HOXA-11 genes are members of the homeobox genes subclass. Their expression is observed in glands and stroma of endometrium throughout the menstrual cycle, and their maximal expression is observed during the implantation window. Objective: The study was designed to answer the question whether the infertility in endometriosis patients could be caused by decreased expression of HOXA-10 and HOXA-11 genes in endometrium. Material and method: Biological material consisted of endometria obtained from 13 patients with endometriosis,10 women with idiopathic infertility and 17 patients in the control group. In all patients surgery was performed during the implantation window, 7-9 days after ovulation. The endometrial biopsies were obtained by Pipell or during hysteroscopy. The expression of analyzed genes was assessed using RT-PCR method. Results: In endometrium of women with endometriosis we found lower HOXA-10 and HOXA-11 gene expression compared to patients from both control and idiopathic infertility groups. However, there was no statistical significance. Significant positive correlations (p< 0.0001) were found between HOXA-10 and HOXA-11 expression in all analyzed groups. Conclusions: Skewed expression of HOXA-10 and HOXA-11 during the mid-luteal phase in women with endometriosis could be one of the aetiological factors of infertility in this group of women.